2015
DOI: 10.1177/1065912915605904
|View full text |Cite
|
Sign up to set email alerts
|

See Hillary Clinton, Nancy Pelosi, and Sarah Palin Run? Party, Ideology, and the Influence of Female Role Models on Young Women

Abstract: Previous research suggests that women’s descriptive representation may have a role-model effect on young women, encouraging them to greater levels of political participation. Using data from the Monitoring the Future Survey and the National Survey of Political and Civic Engagement of Young People, we examine whether highly visible female role models like Hillary Clinton, Nancy Pelosi, and Sarah Palin, and viable female candidates for governor and senator had a role-model effect on young women. At the national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…We have argued that, despite a certain 'spirit' of agency and achievement, the extent to which the gendered ideal modelled by business celebrities may have a sustainable impact on women's advancement in the workplace may be rather limited. Current research (Cheryan et al, 2011;de Vries, Webb and Eveline, 2006;Mariani et al, 2015;Sealy and Singh, 2010) indicates that long-lasting sustainable change in generating women's advancement happens when women are encouraged to recognize and challenge gender barriers, rather than focus on changing their individual behaviour. The books suggest that, if women emulate this 3Cs ideal, it is entirely possible to jump over, manage or push through gender workplace barriers.…”
Section: Discussionmentioning
confidence: 99%
“…We have argued that, despite a certain 'spirit' of agency and achievement, the extent to which the gendered ideal modelled by business celebrities may have a sustainable impact on women's advancement in the workplace may be rather limited. Current research (Cheryan et al, 2011;de Vries, Webb and Eveline, 2006;Mariani et al, 2015;Sealy and Singh, 2010) indicates that long-lasting sustainable change in generating women's advancement happens when women are encouraged to recognize and challenge gender barriers, rather than focus on changing their individual behaviour. The books suggest that, if women emulate this 3Cs ideal, it is entirely possible to jump over, manage or push through gender workplace barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Since the majority of students in this study were white, their white privilege may have caused cultural or racial dissonance that inhibited social justice action (Cabrero, 2012; Robbins, 2016). An alternative explanation is tied to the literature reporting that women are less involved in politics (Mariani, Marshall, & Mathews-Schultz, 2015). Women in the United States have only had the right to vote for 98 years, and women leaders are grossly underrepresented in U.S. national political races and seats, although the 2018 election showed an increase in women running for political office.…”
Section: Discussionmentioning
confidence: 99%
“…Campbell and Wolbrecht (2006, 233) conclude that "the presence of visible female role models does in fact increase the propensity for girls to express an intention to be politically active. " Mariani, Marshall, and Mathews-Schultz (2015) found a positive effect of very prominent female politicians on young women's political participation, whereas Hoyt and Simon (2011) emphasize the importance of role models being "non-elite," that is, easier to identify with. Ladam, Harden, and Windett (2016) found that electing a female governor has a significant effect on the number of female candidates for the state legislature.…”
Section: Do Role Models Increase Women's Political Ambition?mentioning
confidence: 99%
“…In this paper, we focus on gender role models. Based on evidence from observational studies, it is widely believed that exposure to role modelspoliticians of the same gender with which potential aspirants can identifyhas a positive effect on political engagement (Campbell and Wolbrecht, 2006;Fridkin and Kenney, 2014;Lawless and Fox, 2010;Mariani, Marshall, and Mathews-Schultz, 2015;Wolbrecht and Campbell, 2007), as well as on political ambition more specifically (Beaman et al, 2009(Beaman et al, , 2012Ladam, Harden, and Windett, 2016). Significantly fewer studies report null findings or conditional effects (Broockman, 2014;Clayton, 2015;Gilardi, 2015).…”
Section: Introductionmentioning
confidence: 99%